2008
DOI: 10.1111/j.1365-2842.2008.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification and management of chronic sialadenitis of the parotid gland

Abstract: Saliva has numerous oral functions and multiple functions in relation to digestion in the upper gastrointestinal tract. Chronic salivary hypofunction can lead to severe adverse health outcomes. Chronic sialadenitis is one of the major conditions that can cause salivary hypofunction. A correct diagnosis and management of chronic sialadenitis is essential for the recovery of salivary hypofunction. Chronic sialadenitis of the parotid gland is often seen in the clinic, sometimes also referred to as recurrent pyoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 46 publications
0
36
0
1
Order By: Relevance
“…[14][15][16] The management of such cases requires removal of the obstruction. 16,17 Endoscopy-assisted dilation and irrigation of the ducts are commonly used for nonstone causes, whereas sialo-lithotripsy is applied in cases of stones. In cases of radioiodine-induced sialadenitis, sialography depicted stenosis in the main duct and irregular expansion in the bifurcating ducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] The management of such cases requires removal of the obstruction. 16,17 Endoscopy-assisted dilation and irrigation of the ducts are commonly used for nonstone causes, whereas sialo-lithotripsy is applied in cases of stones. In cases of radioiodine-induced sialadenitis, sialography depicted stenosis in the main duct and irregular expansion in the bifurcating ducts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the stent could prevent the stenosis caused by edema. 17,18 The hollow stent allowed saliva to flow out concurrently. The stent was usually removed 2 weeks after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 of 19 patients (26.3%) in the US database with multigland involvement met the serologic and pathologic criteria for Sjö gren syndrome. A previous long-term follow-up study 12 in Beijing, China, among patients with chronic sialadenitis of the parotid gland found that 12 of 22 patients (54.5%) in whom Sjö gren syndrome was ruled out at initial presentation went on to develop the disorder after a mean follow-up time of 5.2 years. Seronegative patients with chronic sialadenitis are likely being referred for salivary endoscopy in the United States because of lack of other viable diagnostic and therapeutic alternatives.…”
Section: Commentmentioning
confidence: 98%
“…Of the salivary glands, the parotid gland (PG) most frequently produces symptoms after 131 I therapy, and is known to be more radiosensitive than the submandibular salivary gland (10). External massage of the PG is presumed to be helpful in preventing parotid dysfunction after 131 I therapy (3,(11)(12)(13), because it is believed to ''milk out'' accumulated 131 I into the oral cavity, and thus, reduce radiation risks. However, no evidence has been presented that the massage of the PG actually reduces radioisotope accumulation in the PG.…”
Section: H Igh-dosementioning
confidence: 99%